Turkey’s energy strategy: Synchronizing geopolitics and foreign policy with energy security - Bilgin, Mert (SETA Foundation, 2015)
This article analyzes Turkey’s official energy strategy to indicate how it responds to actual challenges by striking a compromise between market characteristics, and geopolitics and foreign policy. It points to Turkey’s growing energy demand as one of the most significant factors that affect the country’s policies and elaborates how Turkey’s supply security perspective intersects with geopolitical features and foreign policy issues on behalf of international cooperation. The first section, with conceptual highlights, gives a brief picture of the actual energy security challenges that Turkey faces. The second part focuses on Turkey’s official energy strategy (Turkey’s Energy Strategic Plan, as introduced by the Ministry of Energy and Natural Resources) to understand how these policies respond to the challenges Turkey faces. The final section gives an idea of how Turkey’s energy security strategy supports international cooperation with diverse actors.
Keywords: Energy Strategy; Geopolitics; Foreign Policy